Macrocyclic lactones in antiparasitic therapy - Vercruysse, J.; Rew, R. S.; Rew, R. S.; Vercruysse, J. (Wallingford :CAB International, 2002)
This book contains 14 chapters on macrocyclic lactones (MLs). Chapter 1 covers chemistry, pharmacology and drug safety and chapter 2 deals with pharmacokinetics. New information on the mode of action emphasizing glutamate-gated chloride ion channels are reviewed in chapter 3. The impact of MLs on dung fauna is described in chapter 4. Chapter 5 reviews resistance mechanisms and field resistance. The use of MLs to control parasites of cattle is discussed in several sections in chapter 6. The next seven chapters deal with ML use in sheep and goats, horses, pigs, dogs and cats, wild ruminants, exotic pets and man, respectively. Finally, chapter 14 examines scientific, social, political and economic issues that control the future of MLs. The likely readership is composed of researchers and veterinarians.
Keywords: HH405 - Pesticides and Drugs; Control, (New March 2000); HH410 - Pesticide and Drug Resistance; LL822 - Protozoan, Helminth, Mollusc and Arthropod Parasites of Animals, (New March 2000); LL882 - Veterinary Pharmacology and Anaesthesiology, (New March 2000); VV220 - Protozoan, Helminth and Arthropod Parasites of Humans, (New March 2000)